Using network models in person-centered care in psychiatry: How perspectivism could help to draw boundaries - de Boer, Nina S.; Kostić, Daniel; Ross, Marcos; de Bruin, Leon; Glas, Gerrit (Frontiers in Psychiatry, 2022)
In this paper, we explore the conceptual problems arising when using network analysis in person-centered care (PCC) in psychiatry. Personalized network models are potentially helpful tools for PCC, but we argue that using them in psychiatric practice raises boundary problems, i.e., problems in demarcating what should and should not be included in the model, which may limit their ability to provide clinically-relevant knowledge. Models can have explanatory and representational boundaries, among others. We argue that we can make more explicit what kind of questions personalized network models can address in PCC, given their representational and explanatory boundaries, using perspectival reasoning.